2018
DOI: 10.3126/jpan.v7i2.24610
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Causing Delay in Help Seeking Behavior in Patients With Mental Illness

Abstract: Introduction: Stigma is a sign of disgrace or discredit that sets a person apart from others. Stigma has detrimental effect on stigmatized persons’ life which may even hamper or delay the help seeking behavior, which ultimately increases the duration of untreated mental illness. Material And Method: A cross sectional survey was conducted among 90 psychiatry outpatients attending Manipal Teaching Hospital, Pokhara, Nepal. Discrimination and disclosure sub-scale of the Stigma scale and ISMI- 10 was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Most of the qualitative studies with stigma as the major theme or domain focused on public stigma of either general community members or healthcare workers. Quantitative or mixed methods studies predominantly focused on self or internalised stigma of people with lived experiences of mental disorders (PWLE) (Adhikari, 2015; Neupane et al ., 2016; Amatya et al ., 2018; Rathod et al ., 2018; Maharjan and Panthee, 2019; Shrestha, 2019), public stigma (family and community members) (Neupane et al ., 2016; Amatya et al ., 2018; Koirala et al ., 2019; Luitel et al ., 2019; Pandey, 2019), health workers’ stigma (Gartoulla et al ., 2015; Pathak and Montgomery, 2015; Kohrt et al ., 2018 b , 2020), medical and pharmacy students’ stigma (Panthee et al ., 2010; Adhikari, 2018; Jalan, 2018; Shakya, 2018), and perceived stigma among PWLE and family members (Adhikari et al ., 2008; Lamichhane, 2019). Four studies exclusively focused on courtesy stigma (Angermeyer et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the qualitative studies with stigma as the major theme or domain focused on public stigma of either general community members or healthcare workers. Quantitative or mixed methods studies predominantly focused on self or internalised stigma of people with lived experiences of mental disorders (PWLE) (Adhikari, 2015; Neupane et al ., 2016; Amatya et al ., 2018; Rathod et al ., 2018; Maharjan and Panthee, 2019; Shrestha, 2019), public stigma (family and community members) (Neupane et al ., 2016; Amatya et al ., 2018; Koirala et al ., 2019; Luitel et al ., 2019; Pandey, 2019), health workers’ stigma (Gartoulla et al ., 2015; Pathak and Montgomery, 2015; Kohrt et al ., 2018 b , 2020), medical and pharmacy students’ stigma (Panthee et al ., 2010; Adhikari, 2018; Jalan, 2018; Shakya, 2018), and perceived stigma among PWLE and family members (Adhikari et al ., 2008; Lamichhane, 2019). Four studies exclusively focused on courtesy stigma (Angermeyer et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The review identified a number of manifestations of mental disorders. Studies reported the prevalence of self-stigma ranging from 34 to 54% of patients in psychiatric Outpatient Department (OPD) of national hospitals, and 80% of persons screening positive for alcohol use disorder in the community reported internalised stigma (Amatya et al ., 2018; Maharjan and Panthee, 2019; Shrestha, 2019). The patients scored high on components such as stereotype endorsement, discrimination experience and social withdrawal.…”
Section: Resultsmentioning
confidence: 99%